Exceptionally Upsetting How Americans Are Increasingly Confusing Knowledge with Opinion and What Can Be Done about It. - Burton, Howard (Open Agenda Publishing, 2021)
As American society becomes more polarized by the day, the question of how this ""exceptional nation"" can hope to regain its mojo is more pressing than ever before. With his unique blend of wry humor and clear-headed analysis, Howard Burton wades into America's partisan fray, weaving together historical investigation, pop culture and a passionate belief in the country's true strengths in order to develop a concrete way out of the current culture war. From an outsider's perspective, Burton examines how the writings and beliefs by the Founding Fathers and Adam Smit are often quite different fro.